Test of G. E. Type H, Transformer - Blachly, C. Paul; Fielding, Lathrop Weaver (My University, 1905)
Introduction: Alternating current phenomena are at the present time approaching a stage of development which, when reached, may be considered the master means for the control of power and illumination. Since a great part of the water power in the United States is being utilized by the engineer and converted into electrical energy and transmitted at high voltages to distant cities. Herein lies the use of the alternating current transformer. A static transformer is a continuous laminated iron core interlinked with two electrical circuits, one of which receives electrical energy and the other delivers electrical energy. Fig. 2, Plate H. represents a simple transformer. The coil which receives the electrical energy or that one over which the E.M.F. is first impressed is called the primary, and that coil which delivers electrical energy is called the secondary. Fig.'s 3 and 4, Plate H. represent diagrammatically the core and shell types respectively. If the electric circuits surround the magnetic circuit as in (3) the transformer is said to be of the core type. If the reverse is true as in (4) it is of the shell type. The ratio of transformation is designated by the ratio of the number of turns in the secondary winding to the number in the primary winding. If this ratio is greater than unity the transformer steps up the voltage, and if less than unity steps down the voltage. The one extensive use of the transformer lies in the fact that electrical energy may be taken into the primary winding and delivered from the secondary at a different pressure.
Citation: Blachly, C. Paul, Fielding and Lathrop Weaver. Test of G. E. Type H, Transformer. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Hystersis Loss; Copper Drop; Steinmetz Diagram; Theses